2021
DOI: 10.3390/antiox10122031
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of Bee Bread in Metabolic Dysfunction-Associated Fatty Liver Disease (MAFLD) Rats: Impact on Oxidative Stress and Inflammation

Abstract: Metabolic dysfunction-associated fatty liver disease (MAFLD) is a pathological accumulation of hepatic lipid closely linked with many metabolic disorders, oxidative stress and inflammation. We aimed to evaluate the hepatoprotective effect of bee bread on oxidative stress and inflammatory parameters in MAFLD rats. Twenty-eight male Sprague-Dawley rats were assigned into four groups (n = 7/group): normal control (NC), high-fat diet (HFD), bee bread (HFD + Bb, HFD + 0.5 g/kg/day bee bread) and orlistat (HFD + Or,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 98 publications
6
13
0
Order By: Relevance
“…The present study demonstrated significant increases in the Lee obesity index and body weight gain in the obese group than those in the control group, which are consistent with our previously published reports [ 40 , 78 ]. Furthermore, excess energy or calorie intake following consumption of HFD led to an increased accumulation of lipids in the adipocytes, hence resulting in an increased Lee obesity index and body weight gain in this group, as reported by previous studies [ 33 , 37 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The present study demonstrated significant increases in the Lee obesity index and body weight gain in the obese group than those in the control group, which are consistent with our previously published reports [ 40 , 78 ]. Furthermore, excess energy or calorie intake following consumption of HFD led to an increased accumulation of lipids in the adipocytes, hence resulting in an increased Lee obesity index and body weight gain in this group, as reported by previous studies [ 33 , 37 ].…”
Section: Discussionsupporting
confidence: 94%
“…H. itama bee bread was able to reduce these parameters significantly although no changes in food and calorie intakes were observed in this group, compared to the obese group. These results demonstrated the anti-obesity effect of H. itama bee bread in which it increased weight loss without reducing the food intake; hence, these results were in line with previous published studies [ 33 , 37 , 40 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These high antioxidant values come mainly from the banana peel, which, in its unripe stage, contains a large amount of phenolics and flavonoids (Borges et al, 2020; Savlak et al, 2016). Phenolics and flavonoids are secondary plant‐based food metabolites, which are a class of natural antioxidants mostly found in foods and have lipid‐lowering and anti‐obesity effects (Zakaria et al, 2021). Here, the flour used was made from the skin and pulp in its unripe stage, which conferred a high antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%